Geochemistry of sediments from the continental slope of the Ross Sea, Antarctica, supplementary data to: Ceccaroni, L; Frank, Martin; Frignani, M; Langone, Leonardo; Ravaioli, Mariangela; Mangini, Augusto (1998): Late Quaternary fluctuations of biogenic component fluxes on the continental slope of the Ross Sea, Antarctica. Journal of Marine Systems, 17(1-4), 515-525 - Ceccaroni, L; Frank, Martin; Frignani, M (PANGAEA - Data Publisher for Earth & Environmental Science, 1998)
A sediment core, collected from the western part of the continental slope of the Ross Sea at 2380 m water depth, records events of the last two climatic cycles (250 kyr). A 230Thex-based chronology was obtained and boundaries of the isotope stages were set assuming that biological productivity was enhanced during periods of less ice cover. Then, 230Thex0, organic carbon, biogenic silica and biogenic Ba distributions were compared to the glacial-interglacial stage boundaries and corresponding ages of the delta18O record of Martinson et al. [Martinson et al., 1987, doi:10.1016/0033-5894(87)90046-9]. Sediment accumulation rates ranged between 1.2 cm kyr**-1 in the isotope stage 6 and 3.8 cm kyr**-1 during the Holocene. Variations in the concentrations and fluxes of organic carbon, biogenic Ba, biogenic silica and Mn gave information on palaeoclimate changes. Processes of sediment redistribution in the Ross Sea margin were enlightened from a comparison of the measured and expected fluxes of 230Thex. Calculation of the focusing-corrected accumulation rates of biogenic Ba enabled us to evaluate the export palaeoproductivity. Corrected accumulation rates of biogenic components and calculated palaeoproductivities were low, compared to the Antarctic Polar Front in the Atlantic sector, throughout the last two climatic cycles. Glacial-interglacial changes of sea ice cover and ventilation of the Ross Sea were probably major causes of variations in biogenic particle flux and distribution of redox-sensitive elements within the sediment column.
This dataset is supplement to doi:10.1016/S0924-7963(98)00061-X
Keywords: Datensammlung